An exposure of professional meaningful coordinating capabilities of students-teachers - Kolumbet A.N (Kharkov National Pedagogical University, 2013)
Purpose - to identify the motor abilities of students who have the greatest impact on the success of teaching. The experiment involved 264 students. It is established that the speed of operational thinking, the ability to quickly and accurately respond to the resulting job and do it exactly the goal has a positive effect on the quality of teaching. There is a high correlation with reactive and kinesthetic abilities and pedagogical skills. It was found that the speed, shift and focus of attention is closely linked to the ability to attention, memory, fidelity to the information received. It is proved that for a successful career students need to develop kinesthetic responsive coordination abilities and the ability to orient in space. It is recommended for software development content of physical education to focus on improving the coordination abilities listed.